Syarat Sahnya Suatu Jual-Beli Online Pada Perjanjian/ Kontrak Elektronik Di Indonesia - Samuel Situmorang (Visi Sosial Humaniora, 2022)
The development of technology is very fast and has resulted in social change at this time. Bassicly, social change arise because humans are dynamic to fullfil needs. Before the advent of the internet, sellers and buyers could only trade in conventional markets. Now, internet has become a place for sellers to offer products and can be seen and purchased directly by buyers. Sellers and buyers meet via internet and carry out electronic commerce activities. Laws are fast in responding to technological developments can certainly result in strong regulations in the field of electronic information and transaction. Electronic contract is an agreement made through the electronic systems. Every agreement in Indonesian law requires certain conditions to be valid. The conditions that are required for the validity of agreements in Indonesian laws are something to discussed in relation to development of technology electronic information and transactions. Keywords: Cyberlaw, E-Commerce, E-Contract.